Applied Welfare Economics with Discrete Choice Models - Small, Kenneth A.; Rosen, Harvey S. (Econometrica, 1981)
Economists have been paying increasing attention to the study of situations in which csumers face a discrete rather than a continous set of choices.Such models are potentially very important in evaluating the impact of government programs upon consi.mterwelfare.But very little has been said in general regarding the tools of applied welfare economics in discrete choice situations.This paper shows how the conventional methods of applied welfare economics can be modified to handle such cases.It focuses on the cornputation of the excess burden of taxation, and the evaluation of gua].itychange.The results are applied to stochastic utility models, including the popular cases of prohit and logit analysis.Throughout, the ernp)-asis is on providing rigorous guidelines for carrying out applied work.